Molecular Evolution of Transforming Growth Factor-β (TGF-β) Gene Family and the Functional Characterization of Lamprey TGF-β2 - Liu, Siqi; Guo, Junfu; Cheng, Xianda; Li, Wenna; Lyu, Shuangyu; Chen, Xuanyi; Li, Qingwei; Wang, Hao (Frontiers in Immunology, 2022)
The transforming growth factor-βs (TGF-βs) are multifunctional cytokines capable of regulating a wide range of cellular behaviors and play a key role in maintaining the homeostasis of the immune system. The TGF-β subfamily, which is only present in deuterostomes, expands from a single gene in invertebrates to multiple members in jawed vertebrates. However, the evolutionary processes of the TGF-β subfamily in vertebrates still lack sufficient elucidation. In this study, the TGF-β homologs are identified at the genome-wide level in the reissner lamprey (Lethenteron reissneri), the sea lamprey (Petromyzon marinus), and the Japanese lamprey (Lampetra japonica), which are the extant representatives of jawless vertebrates with a history of more than 350 million years. The molecular evolutionary analyses reveal that the lamprey TGF-β subfamily contains two members representing ancestors of TGF-β2 and 3 in vertebrates, respectively, but TGF-β1 is absent. The transcriptional expression patterns show that the lamprey TGF-β2 may play a central regulatory role in the innate immune response of the lamprey since it exhibits a more rapid and significant upregulation of expression than TGF-β3 during lipopolysaccharide stimuli. The incorporation of BrdU assay reveals that the lamprey TGF-β2 recombinant protein exerts the bipolar regulation on the proliferation of the supraneural myeloid body cells (SMB cells) in the quiescent and LPS-activated state, while plays an inhibitory role in the proliferation of quiescent and activated leukocytes in lampreys. Furthermore, caspase-3/7 activity analysis indicates that the lamprey TGF-β2 protects SMB cells from apoptosis after serum deprivation, in contrast to promoting apoptosis of leukocytes. Our composite results offer valuable clues to the origin and evolution of the TGF-β subfamily and imply that TGF-βs are among the most ancestral immune regulators in vertebrates.